Spatial and temporal dynamics of irrigation water quality under drought conditions in a large reservoir in Southern Portugal - Tomaz, Alexandra (2021)
Water is a scarce resource in the Mediterranean region where adverse climatic conditions promoting water shortages tend to increase with climate change. Under water scarcity conditions and high atmosphere evaporative demand, the risks of decreased water quality, and land salinization are major threats to the sustainability of irrigated agriculture in this region. The assessment of the quality of irrigation water is increasingly important to ensure the maintenance of long-term salt balance at a crop, farm, and regional scale. This study is focused on the spatial and temporal variability of water quality for irrigation in the Alqueva reservoir (Southern Portugal). The assessment was performed every 2 months during a distinctive drought year (2017) and included inorganic ions (Na+, Ca2+, Mg2+, K+, NH4 +, Cl−, F−, SO4 2−, NO3 −, and NO2 −), pH, and electric conductivity (ECW) of water. Sodium adsorption ratio (SAR) was calculated, and potential soil permeability problems were estimated. The assessment showed significantly higher values of the physicochemical parameters in the most upstream sites, located near tributaries inflows, and an upward trend in ion concentrations throughout the year, with significantly higher concentrations of Na+, Mg2+, Cl−, and SO4 2, registered through May to November, reflecting the severe drought felt in the summer, autumn, and winter. The evaluation of water quality for irrigation indicated a slight to moderate risk of reduced infiltration rates, which should be considered whenever sprinkler irrigation is used, mainly in fine-textured soils, which are prevalent in the irrigated area. The multivariate statistical approach, using principal component analysis and factor analysis, identified two principal components related to salinity and nutrient concentrations. The cluster analysis revealed three groups of similarity between samples pointing to a more time- than space-controlled pattern. Overall, the temporal dynamics of the water physicochemical parameters could indicate that an abnormal annual distribution of precipitation and temperature may distort seasonal differences. To prevent water and soil degradation, a more frequent assessment of the water quality should be considered, allowing for the selection of appropriate soil and water management measures in irrigated areas